Effect of sleep loss on pain—New conceptual and mechanistic avenues - Kamila Kourbanova; Kamila Kourbanova; Chloe Alexandre; Chloe Alexandre; Alban Latremoliere; Alban Latremoliere (Frontiers in Neuroscience, 2022)
IntroductionSleep disturbances increase pain sensitivity in clinical and preclinical settings, but the precise mechanisms are unknown. This represents a major public health issue because of the growing sleep deficiency epidemic fueled by modern lifestyle. To understand the neural pathways at the intersection between sleep and pain processes, it is critical to determine the precise nature of the sleep disruptions that increase pain and the specific component of the pain response that is targeted.MethodsWe performed a review of the literature about sleep disturbances and pain sensitivity in humans and rodents by taking into consideration the targeted sleep stage (REMS, non–NREMS, or both), the amount of sleep lost, and the different types of sleep disruptions (partial or total sleep loss, duration, sleep fragmentation or interruptions), and how these differences might affect distinct components of the pain response.ResultsWe find that the effects of sleep disturbances on pain are highly conserved among species. The major driver for pain hypersensitivity appears to be the total amount of sleep lost, while REMS loss by itself does not seem to have a direct effect on pain sensitivity. Sleep loss caused by extended wakefulness preferentially increases pain perception, whereas interrupted and limited sleep strongly dysregulates descending controls such as DNIC, especially in women.DiscussionWe discuss the possible mechanisms involved, including an increase in inflammatory processes, a loss of nociceptive inhibitory pathways, and a defect in the cognitive processing of noxious input.